Perancangan Website Tiket Online Bird Park Palembang Menggunakan Design Thinking - Stevany Angel; Obert Sean; Noviana Engelica; Nora Hafildah (Universitas Multi Data Palembang, 2026)
This research aims to design the official website of Palembang Bird Park as an information medium and online ticket booking platform. Palembang Bird Park, located in the Jakabaring area, has significant tourism potential with a collection of over 1,000 birds from various species. However, the conventional information and ticket booking system has become an obstacle in tourism development. This research applies the Design Thinking method, which includes the stages of Empathize, Define, Ideate, Prototype, and Test, to produce a user-centered design. The result is a website prototype with features including destination information, gallery, ticket prices, online ticket booking, and integrated payment system. Testing using the Black Box Testing method shows that all features function properly, with a success rate of 100%.